THE EFFECT OF BALANCE TRAINING ON BALL CONTROL ABILITY IN SOCCER PLAYERS OF SMP NEGERI 3 BAMBEL - Ahlul Fikri; Afrizal; Ladipin (RADJA PUBLIKA, 2025)
This study aims to determine the significant effect of balance training on improving the ball control ability of soccer players at SMP Negeri 3 Bambel. The methodology employed was an experimental method with a one-group pretest-posttest design. The research sample consisted of eleven soccer players selected through a total sampling technique. The instrument used to measure the dependent variable was a ball control skill test. The results of data analysis showed a considerable increase in the average score of ball control ability, from 2.36 in the pretest to 4.27 in the posttest. The statistical t-test resulted in a t-count of 7.95, which is significantly greater than the t-table of 1.81 at ten degrees of freedom and a five percent significance level. Based on the hypothesis testing criteria, this leads to the rejection of the Null Hypothesis (H0) and the acceptance of the Alternative Hypothesis (Ha). Therefore, it can be concluded that balance training has a significant and positive effect on improving the ball control ability of soccer players at SMP Negeri 3 Bambel. This finding underscores the importance of integrating balance training into fundamental soccer training programs for adolescents.